Is it really nephroblastomatosis? Analysis of diagnostic and therapeutic difficulties: case report of three patients - Janeczko-Czarnecka, Małgorzata; Niedzielska-Łoś, Ewa; Bronowicki, Krzysztof; Pietras, Wojciech; Ussowicz, Marek (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Nephroblastomatosis (NB) is the presence of multifocal residues of embryonic kidney localised in the kidney capsule, the cortex, or in the renal core. A characteristic picture of lesions in imaging studies (ultrasound, computed tomography, magnetic resonance imaging) allows us to establish the diagnosis and start chemotherapy. We present a course of treatment in three patients with baseline diagnosis of NB. We emphasise that due to the lack of initial histopathological examination diagnosis of NB only by means of imaging studies can be both a diagnostic and a therapeutic challenge. Close cooperation of specialists in the fields of radiology, surgery, and paediatric oncology is crucial.